Hubungan Antara Tingkat Stres Dengan Siklus Menstruasi Pada Remaja Siswi Kelas XII SMA Negeri 1 Batam - Cevy Amelia; Acholder Acholder; Syarifah Balqis Shahab (Zona Kedokteran: Program Studi Pendidikan Dokter Universitas Batam, 2022)
Background: Students are demanded by academic achievement in a timely manner, especially class XII students which can be a point of stress, causing menstrual cycles to become irregular. The menstrual cycle can be said to be normal if it is regular every month with a span of about 21-35 days. This study aims to determine the relationship between stress levels and menstrual cycles in class XII students of SMA Negeri 1 Batam in 2021. Methods: This type of research is quantitatifewith research design use a cross sectional approach. The number of samples as many as 66 students, samples were taken using simple random sampling. This research was conducted by giving a questionnaire. The results of the study were analyzed using the Spearman rank test. Results: Data were analyzed by Spearman rank test. There is a level of stress in class XII students with criteria (31.8%) normal stress level, (16.7%) mild stress level, (34.8%) moderate stress level, (13.6%) severe stress level, ( 3.0%) the stress level is very heavy, (47.0%) the menstrual cycle is normal, (53.0%) the menstrual cycle is not normal. In class XII students of SMA Negeri 1 Batam. With a p value of 0.002 (p<0.05). Conclusion: there is a relationship between stress levels and menstrual cycles in class XII students of SMA Negeri 1 Batam in 2021